Marine debris ingestion of green sea turtles, Chelonia mydas, (Linnaeus, 1758) from the eastern coast of the United Arab Emirates. (October 2018) - Yaghmour, Fadi; Al Bousi, Marwa; Whittington-Jones, Brendan; Pereira, John; García-Nuñez, Soledad; Budd, Jane
Abstract: The deleterious effects of marine debris ingestion on marine turtles are well documented in literature globally. In this study, the qualitative and quantitative aspects of marine debris ingested by 14 stranded green sea turtles Chelonia mydas, (Linnaeus, 1758) along the eastern coast of the United Arab Emirates were investigated. The numeric and gravimetric proportions of debris in the esophagus, stomach and intestines were documented following classification of color, presumed sources and Marine Strategy Framework Directive categories and sub-categories. The results show that 85.7% of the specimens examined consumed marine debris. On average, specimens consumed 61.9 ± 17.2 items of 1.0 ± 0.3 g mass. Plastics, particularly white, and transparent thread-like and sheet-like plastics, were the predominant debris ingested. The results reflect a potentially high level of interaction between green sea turtles and anthropogenic marine debris along the Gulf of Oman coast of the UAE. Highlights: We examined green sea turtles from the Gulf of Oman Coast of the United Arab Emirates. 14 specimens were examined and marine debris were observed in 85.7% of the examined turtles. The majority of debris ingested were composed of plastics Debris sources included rope, fabric, cotton bud, weaved and regular plastic bag and fishing line, hook, net and trap Our study suggests that a high proportion of turtles interact with substantial quantities of marine debris in the region This indicates that marine debris present a threat to green turtles in the region.